The Role of Charismatic Leadership, Work Environment and Organizational Culture on Improving Employee Performance at the Bangkalan Pratama Tax Service Office - Apriyanto Nugroho; Kuswandi; Sri Rahayu; Rifda Fitrianty (Lead Journal of Economy and Administration, 2025)
Human resources are the most important key to bringing effective and efficient results to an organization. Organizations can improve the performance of their employees if the role of leadership, especially charismatic leadership, the work environment and the existing organizational culture are well implemented in the relevant agencies. This study was conducted to examine employee performance based on the influence of charismatic leadership, work environment and organizational culture. The sample in this study were 77 employees at the Bangkalan Primary Tax Service Office. The analytical tool used is multiple linear regression. The results showed that partially the variables of charismatic leadership, work environment and organizational culture had a positive and significant effect on employee performance. Then the results of simultaneous testing of charismatic leadership variables, work environment and organizational culture affect employee performance, at the Bangkalan Pratama Tax Service Office, East Java.